Empowering livestock development: unveiling stakeholders' impact in Besowo Village, Indonesia's nature reserve buffer zone - Man, Norsida; Siti Azizah; Shofiyyah, R.; Djunaidi, Irfan H.; Rachmawati, A.; Mukaromah, Anif (Zhongguo Hangtian Gongye Zonggongsi, 2024)
Objective: The objective of this research was to identify stakeholders contributing to the advancement of livestock business in Besowo Village, ascertain the nature of stakeholder interactions, and propose strategies for livestock business growth based on stakeholder decision-making approaches. Method: The study utilized a three-step stakeholder analysis process: initial identification through semi-structured interviews, stakeholder categorization via an interest-influence matrix, and assessment of stakeholder relationships using an actor linkage matrix. Results: The investigation revealed sixteen stakeholders involved in livestock development, categorized into primary and secondary groups. Stakeholders were further classified based on their influence and significance into context setters, subjects, crowds, and key players. Interactions among stakeholders predominantly involved communication, coordination, and cooperation. The consensus decision-making method emerged as the most suitable, ensuring inclusivity of stakeholder interests and participation. Limitations: This study is confined to examining stakeholder roles in livestock business development specifically within Besowo Village. Significance: By offering a stakeholder analysis of livestock business development in rural buffer zones, this research contributes novel insights and proposes effective decision-making approaches.